Main Theme of Feminist under Political thoughts - Abithaa, K. K. (International Journal of English Literature and Social Sciences (IJELS), 2019)
A large amount of feminist writing deals with different aspects of subordination of women and about the political rights for women. Feminist like Karla Marx and his voice for those women’s who are under the control of men. That the main thing of these type of writers who portrait how women’s will get equal rights in this world.